Effect of Ridging and Tie-Ridging Time on Yield and Yield Component of Sorghum in Northern Ethiopia - Worku, Yalelet Abie (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Abstract Water deficit and poor fertility of soil are among the main constraints for sorghum production in northern Ethiopia's semi-arid regions. A field experiment was carried out at Lasta and Sekota districts of the Eastern Amhara Region in Ethiopia to evaluate the effects of Ridging and tie-ridging time on the yield performance of sorghum (Sorghum bicolor). The experiment consisted of eight treatments of ridging time & time of tie (Tie-ridging at planting, Ridge at planting tying 2 Weeks After Planting, Ridge at planting tying 4 Weeks After Planting, Tie-ridging 3 Weeks After Planting, Ridging 2 Weeks After planting & tying 4 Weeks After Planting, Ridge 3 Weeks After Planting & tying 6 Weeks After Planting, Tie-ridging 6 Weeks After Planting); including Shilshalo as a control farmer practice which was arranged in a randomized complete block design (RCBD) with three replication. The experiment revealed that ridging and tie-ridging time has a significant effect on the yield of sorghum. Based on the result,- ridging at planting increased the yield of sorghum by about 37.9 % at Sekota (Aybira) relative to the control (farmer practice), and Tie ridging 3 weeks after planting increased sorghum yield by 30.11% at Lalibela as compared to the control (farmers practice). The highest yield of 3.642 tons/ha and 1.903 tons/ha was obtained from tie ridge at planting for Sekota (Aybira) and tie ridging 3 weeks after planting at Lalibela. Therefore, tie and ridge at planting could be appropriate for sorghum production at Sekota (Aybira) and sorghum growing areas. However, tie-ridge 3 weeks after planting could be appropriate for sorghum production at Lalibela (Kechinabeba) and growing areas.Keywords: - Sorghum, Tie ridge, water deficit and yield